THE ROLE OF AGRICULTURAL EXTENSION WORKERS IN INCREASING CASHEW FARMING PRODUCTIVITY THROUGH CULTIVATION TECHNIQUE IMPROVEMENT EFFORTS IN WAIBAO VILLAGE, TANJUNG BUNGA SUBDISTRICT, EAST FLORES REGENCY - Saleh, Arini Muhamad; Abdurrahman, Mustafa; Mahendra, Bayu (Undana Press, 2025)
This study aims to (1) determine the profile of cashew plantation businesses in Waibao Village, Tanjung Bunga District, East Flores Regency (2) determine the role of extension workers according to farmer’s perceptions in increasing cashew farming productivity through efforts to improve cultivation techniques in Waibao Village, Tanjung Bunga District, East Flores Regency. The results of the study indicate that the profile of cashew farming based on the application of cultivation techniques taught by agricultural extension workers to farmers including watering, fertilization, pest and disease control, and harvesting and post-harvest is very helpful for farmers have implemented cultivation techniques taught by extension workers and the results of the application of these cultivation techniques have an impact on cashew farming productivity. The role of extension workers as aducators in providing information, guiding and motivating farmers in increasing cashew farming productivity through efforts to improve cultivation techniques including control, and harvesting and post-harvest is in the role category with a percentage of 58,94%.